Use of Psychotropic “Pro Re Nata” Medications by Patients Attending the Outpatient Clinic in a Hospital: A Qualitative Exploration - Rajiah, Kingston; Maharajan, Mari Kannan; Ramaya, Hemawathi; Wan Ab Rahman, Wan Nur Asyiken (Frontiers in Medicine, 2021)
Introduction Administration of psychotropic PRN medications is influenced by diverse factors such as legal use of PRN medications, the attitude of patients, personal bias, and stigma towards such medication use. While PRN prescriptions increasing the efficiency of care, and encourage patients to participate in self-care, the use of psychotropic PRN medications by outpatients has raised concerns about its risks of harm, especially for the outpatients. This study explored the use of psychotropic PRN medications by patients attending the outpatient clinic in a hospital. Methods Qualitative in-depth interviews were conducted. Purposeful sampling was done to achieve cases with enriched information. Participants were chosen regardless of their ethnicity and were selected using the database and patient records in the clinic. Patients 18 years of age prescribed PRN psychotropic medications attending outpatient clinics in a hospital were included. Vulnerable patients (e.g. pregnant ladies, prisoners, cognitively impaired individual, AIDS/HIV subjects, terminally ill subjects) were excluded. Results This study revealed the patients’ perspectives and experiences on self-management of psychotropic PRN medications. The themes that emerged were clustered as education and background, knowledge on psychotropic medications, frequency of medication intake, underuse of medication, the overdose of medication, side effects concern, source of information and personal experience. Conclusions Patients’ understanding of medication, inappropriate medication use, cues to action and use of alternatives are the factors that affected the self-management of psychotropic PRN medications by the patients.